Pengaruh Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Pencegahan Fraud pada Persediaan - Dhia Najatu Silva; Muhammad Aufa (Publikasi Indonesia, 2023)
Due to limited supervision as a result of the growth of the company, the inability of a leader to actively supervise the company's activities, thereby not hindering the possibility of fraudulent inventory. The purpose of this study is to test and analyze the effect of internal control and accounting information systems on fraud prevention in PT Swabina Gatra. As well as to find out which variables have an effect among these variables. In this study, it used a quantitative approach using primary data, namely data from a sample used by 30 people, namely the internal audit section, the accounting and financial department and the inventory section. The data collection technique is to use a questionnaire. The analysis technique used is multiple linear regression analysis. The analytical tools used are data quality tests, classical assumption tests and hypothesis tests using the help of the IBM SPSS Statistics 22 application to process data. This study explains the first hypothesis that can be seen that variables from internal control have a significant influence on the prevention of fraud inventory in PT Swabina Gatra. Meanwhile, the results of the second hypothesis test show that the variables of the accounting information system have a significant influence on the prevention of fraud in the inventory of PT Swabina Gatra. Based on the results of the analysis obtained, it can be concluded that internal control and variables of the accounting information system have a significant effect on the prevention of fraud in inventory.